CONTRIBUTION OF ACHARYA NAGARJUNA IN SUSRUTA SAMHITA: A REVIEW - R.Govind Reddy; Sangeeta Sangvikar; Balaji Potbhare; Savita Sharma; Prashant Shinde; Vanmala Wakode (International Journal of Ayurveda and Pharma Research, 2020)
Acharya Nagarjuna was a famous Buddhist Alchemist. Research scholars have faith in more than one Nagarjuna who contributed in the field of philosophy, alchemy, medical and Tantra and few scholars supporting for only one Nagarjuna who as expert in all subjects. In Ayurveda fraternity, it is general belief that Acharya Nagarjuna has composed the Uttarasthana (Uttaratantra) of Susruta Samhita but there are some references which indicates that Acharya Nagarjuna has contributed in Purvardha also. In Uttarasthana (Uttaratantra) of Susruta Samhita there has not mentioned any Alchemy whereas in Maha Kushtha Chikitsa (Purvardha), Ayaskriti has been used which clearly indicates that Acharya Nagarjuna has not only contributed in the Uttarasthan but also in the Purvardha of Susruta Samhita. Balagraha, Kayachikitsa and Bhutavidya have been described in the Uttarsthana of Susruta Samhita. There are many literatures available in Buddhism which has been contributed by Acharya Nagarjuna. If we are having deep knowledge of the Buddhist literature such as Mulmadhyamikakarika, Yuktisastika etc. which has been contributed by Acharya Nagarjuna then it will be easy to know the exact contribution of Acharya Nagarjuna in Susruta Samhitaas well as in Ayurveda. This article deals with the historical study of Acharya Nagarjuna, a great personality and his contribution in Susruta Samhita.